A comprehensive review on recent advancements in d0 ferromagnetic oxide materials. (15th August 2022) - Chouhan, L.; Srivastava, S.K.
Abstract: d 0 ferromagnetic oxide semiconductors have recently been proposed as a potential and alternative material with high Curie temperature ferromagnetism, which is important to realize spintronics devices operable at room temperature. We review the recent development in non-magnetic elements doped d 0 ferromagnetic oxide semiconductors, including SnO2, TiO2, ZnO, ZrO2 and MgO. The experimental and theoretical results from recent literature on these atypical d 0 ferromagnetic materials are discussed, with a particular focus on their magnetic properties.